Customisation framework based on user satisfaction and marketability of Chinese traditional handicraft products - Liu, Haoran (2024)
This research provides an in-depth discussion and validation of a design customisation framework for Chinese traditional handicraft products, aiming to enhance the user satisfaction and marketability. By introducing the new framework, this research intended to help the product designers an effectively combine the user needs and market trends at the early stage of a new Chinese traditional handicraft products design and development process. This research used the quantitative method through surveys. While the respondents involved in this survey acknowledged as handicraft product experts and end-users to obtain the relevant data on user satisfaction and marketability factors. The results identified 51 customisation elements based on user preferences, perceived value and marketability factors that provide the theoretical support for an innovative design of a new Chinese traditional handicraft products toward satisfaction and marketability. Furthermore, the elements also can demonstrate how user needs and marketing strategies can be integrated into product design to enhance the market performance of Chinese traditional handicraft products. The main contribution of this research is proposed a new Product Design Customisation Framework (PDCF). By validating the framework, the research provides a new reference for future innovative design and market development of Chinese traditional handicraft products. Three successful Chinese traditional handicraft products were selected as sampling product assessment to analyse and validate the applicability of a new framework.